Water as a morphogen in landscapes : = L'eau comme morphogène dans les paysages : proceedings of the XVII UISPP World Congress (1-7 September 2014, Burgos, Spain).. Volume 4/Session A14 - International Union of Prehistoric and Protohistoric Sciences (2016)
Water as generator of networks was the core topic of the second session organized by the commission Theory and Methods in Landscape Archaeology: Archeogeography that began in 2011 on occasion of the Florianopolis Congress.